Effects of molecular flexibility and head group repulsion on aramid amphiphile self-assembly. Issue 12 (12th November 2021) - Kaser, Samuel J.; Lew, Andrew J.; Kim, Dae-Yoon; Christoff-Tempesta, Ty; Cho, Yukio; Ortony, Julia H.
Abstract : Strongly interacting amphiphilic molecules self-assemble in water. The flexibility of the amphiphiles and their head group repulsion mediate their nanostructure geometry. Abstract : The self-assembly of amphiphilic molecules in water has led to a wide variety of nanostructures with diverse applications. Many nanostructures are stabilized by strong interactions between monomer units, such as hydrogen bonding and π–π stacking. However, the morphological implications of these strong, anisotropic interactions can be difficult to predict. In this study, we investigate the relationships between molecular flexibility, head group repulsion, and supramolecular geometry in an aramid amphiphile nanostructure that is known to exhibit extensive hydrogen bonding and π–π stacking – features that give rise to their unusual stability. We find by electron microscopy that increasing backbone flexibility disrupts molecular packing into high aspect-ratio nanoribbons, and at the highest degree of flexibility long-range ordering is lost. Even when backbone rigidity favors tight packing, increasing head group charge through pH-modulation leads to intermolecular electrostatic repulsion that also disrupts close packing. Spectroscopic measurements suggest that these changes are accompanied by disruption of π–π stacking but not hydrogen bonding. Backbone rigidity and head group repulsion are thus important design considerations for controlling internal stability and nanostructure curvature in supramolecular assemblies stabilized by π–π stacking interactions.